The Effect of Smoking on the Immune Microenvironment and Immunogenicity and Its Relationship With the Prognosis of Immune Checkpoint Inhibitors in Non-small Cell Lung Cancer - Sun, Yueqin; Yang, Qi; Shen, Jie; Wei, Ting; Shen, Weitao; Zhang, Nan; Luo, Peng; Zhang, Jian (Frontiers in Cell and Developmental Biology, 2021)
Background: The emergence of immune checkpoint inhibitors (ICIs) has opened a new chapter for the treatment of non-small cell lung cancer (NSCLC), and the best beneficiaries of ICIs treatment are still being explored. Smoking status has been repeatedly confirmed to affect the efficacy of ICIs in NSCLC patients, but the specific mechanism is still unclear. Methods: We performed analysis on the Memorial Sloan Kettering Cancer Center (MSKCC) clinical NSCLC cohort receiving ICIs treatment, The Cancer Genome Atlas (TCGA)-Pang lung cancer cohort and Gene Expression Omnibus (GEO) database GSE41271 lung cancer cohort that didn't receive ICIs treatment, including: survival prognosis, gene mutation, copy number variation(CNV), immunogenicity, immune microenvironment, explored the impact of smoking status on the prognosis of NSCLC patients treated with ICIs and possible mechanism. In addition, 8 fresh NSCLC surgical tissue samples were collected for Mass Cytometry (CyTOF) experiments to further characterize the immune characteristics and verify the mechanism. Result: Through the analysis of the clinical data of the NSCLC cohort treated with ICIs in MSKCC, it was found that the smokers in NSCLC receiving ICIs treatment had a longer Progression-Free Survival (PFS, HR: 0.69, 95% CI: 0.49-0.97, P=0.031) than those who never smoked. Further analysis of the TCGA and GEO validation cohorts found that the differences in prognosis between different groups may be related to the smoking group's higher immunogenicity, higher gene mutations, and stronger immune microenvironment. The results of the CyTOF experiment further found that: the immune microenvironment of smoking group was characterized by higher expression of immune positive regulatory chemokine, and higher abundance of immune activated cells, including follicular helper CD4+ T cells, gamma delt CD4+ T cells, activated DC, and activated CD8+ T cells. In contrast, the immune microenvironment of non-smoking group was significantly enriched for immunosuppressive related cells, including regulatory T cells and M2 macrophages. Finally, we also found highly enriched CD45RAhighCD4+ T cells and CD45RAhighCD8+ T cells in the non-smoking group. Conclusions: Our research results suggest that among NSCLC patients receiving ICIs treatment, the stronger immunogenicity and activated immune microenvironment of the smoking group make their prognosis better.